Integrating Tawhidi String Relation into Village Innovation Programs - Kholison, Rohmatul Farohah; Fitrianto, Achmad Room; Hendratmi, Achsania; Pertiwi, Tanza Dona; Hikmah, Lailatul (Jurnal Ekonomi Syariah Teori dan Terapan, 2024)
The Tawhidi String Relation (TSR) technique is being used in this descriptive qualitative study. This approach uses a shuratic process (interaction, integration, and evolutionary process) to analyze data based on actual field observations. The author of this study examines the role that creativity and innovation programs play in helping the Gosari Gresik community achieve its Villages's Sustainable Development Goals (SDGs). The concept of Islamic Development Economics, which derives from Tawhid philosophy, is the foundation of the analytical instrument that was created. The findings of the study indicate that the dialogue and agreement between the primary institutions for village development, such as the village administration and community and religious leaders, in addressing issues in the village is what causes the process of interaction and integration to occur. The development and execution of creativity and innovation programs in Gosari village heavily relies on these community actors. The six elements of maqashid sharia”hifdz ad-diin, hifdz al-'aql, hifdz an-nafs, hifdz an-nasl, hifdz al-maal, and hifdz al-bi'ah”are all met by the participatory development process, each of which is connected to the others. Then, as the evolutionary process progresses, people's perspectives gradually alter and village labor programs get better as time goes on.